Response to Pneumococcal Polysaccharide and Protein-Conjugate Vaccines Singly or Sequentially in Adults who have Recovered from Pneumococcal Pneumonia - Musher, Daniel M. (2008)
BACKGROUND: Controversy persists over the benefits of pneumococcal polysaccharide vaccine (PPV) in at-risk adults. We studied PPV, protein-conjugate pneumococcal vaccine (PCV), or immunologic ‘priming’ with PCV followed by ‘boosting’ with PPV in adults who recovered from pneumococcal pneumonia. METHODS: Subjects received PPV followed in 6 months by PCV, or vice-versa. IgG to capsular polysaccharide and opsonophagocytic killing activity (OPK) were studied at baseline, 4–8 weeks and 6 months after each vaccination. RESULTS: PPV and PCV stimulated similar IgG levels and OPK at 4–8 weeks. Six months post-PPV, antibody declined to baseline but remained modestly elevated post-PCV. PCV given 6 months post-PPV stimulated modest IgG increases that failed to reach post-PPV peaks. In contrast, PPV 6 months after PCV caused dramatic increases in IgG and OPK to all polysaccharides, consistent with a booster effect. Six months after the second vaccination, however, IgG and OPK in all patients fell precipitously, returning toward original baseline levels. CONCLUSIONS: In high-risk subjects, the effect of PPV is short-lived; PCV stimulates a more prolonged response. PPV as a booster following PCV causes early antibody rises, but IgG declines rapidly thereafter, consistent with induction of suppressor cells or tolerance. Protein vaccines may be needed for high-risk adults.